Internal Control System - Munira, Hijratil; Hazmi, Yusri; Ramadhani, Zuhratul Dinda; Syahira, Cut Yulia (Eastasouth Institute, 2024)
This article discusses how important internal control is for accounting information systems. An internal control system is the responsibility of a company's management, a responsibility that includes creating and maintaining it in accordance with the company's needs. The research method used in writing this article is library research. The data collection technique used is library study, namely data collection is carried out by reviewing reference books in the library. The type of data used is secondary data in the form of books related to the discussion. Data analysis uses descriptive methods, namely describing research results and then drawing conclusions. The conclusion drawn from this article is that to create internal control within the company, it is necessary to obtain quality employees who are in accordance with their responsibilities. The responsibility for developing and operating good internal accounting controls within the company lies in the hands of top management, because the management of funds from company owners is in the hands of top management. In this case, internal control has an important role in company management.